Self-reported questionnaire on periodontal condition validated for use in Brazil - Roberto Pereira Pimentel; Liana Flores Bittencourt; Luisa Martins Miller; Rogério Boff Borges; Rui Vicente Oppermann; Sabrina Carvalho Gomes (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: There is a current expectation of instruments for periodontal condition surveillance worldwide. The present study aimed to validate the Oral Health Questions Set B (OHQB) for the Brazilian Portuguese and evaluate its temporal stability. This is a sequential mixed-method investigation. After the forward-backward translation process to the Brazilian Portuguese, the OHQB Brazil (OHQB-Br) was applied to 156 participants (39.5 ± 14.14 years; 51.9% males). In sequence, through a full-mouth six-sites/teeth examination and in accordance with the original instrument, the periodontal diagnosis was obtained (March 2020). In January 2021, the OHB-BR was reapplied (n = 71). Ordinal alpha and McDonald's omega tested the internal consistency of the OHQB-Br. Temporal stability was investigated [Spearman correlation, intraclass correlation coefficient (ICC), and the Bland-Altman]. The concurrent validity was also verified, considering the periodontal clinical diagnosis (Kruskal Wallis). The ordinal alpha (0.69) and McDonald's omega (0.73) coefficients showed an adequate internal consistency of the OHQB-Br. The OHQB-Br temporal stability was high, as demonstrated by the Spearman coefficient (0.80) and ICC (0.79) and by the Bland-Altman plot. A concurrent validity showed a direct relationship between the OHQB-Br and the clinical condition of no periodontitis, mild, moderate, and severe periodontitis (p < 0.05). Because the OHQB-Br shows internal validity, temporal stability, and adequately identifies periodontal health and moderate/severe periodontitis, the instrument might represent an important tool, at the public level or other settings, for periodontal surveillance in Brazil.